Interpretation Of The Image Of A Woman In Literature - Qahharova, Dilafro‘z Abdug‘afforovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the artistic interpretation of the image of a woman in Uzbek literature, her social, spiritual and aesthetic image in different periods. It also covers the changing nature of the female figure, the connection of the image of a woman in modern literature with independence, will and national values. The article analyzes the artistic expression of the female psyche and social status based on the works of such creators as Chulpon, Oybek, Zulfiya, Said Ahmad, Togay Murod.